Improvement of Methods for Standardisation of Medicines Based on Aloe arborescens - A. V. Beketova; O. V. Evdokimova; M. N. Lyakina (Регуляторные исследования и экспертиза лекарственных средств, 2022)
Much interest is taken in identification of Aloe arborescens Mill. medicines by a major class of bioactive compounds (anthracene derivatives), as well as in quantitative determination of the compounds belonging to the class, with the same unified method for the entire spectrum from herbal drugs to herbal medicinal products. The aim of the study was to develop a methodological approach and select unified conditions for the identification and assay of anthracene-derived compounds in herbal drugs, herbal drug preparations and herbal medicinal products of Aloe arborescens Mill., observing the principle of holistic, end-to-end standardisation. Materials and methods: analytical conditions were unified using literature data and a comparison of reference values and requirements of the Russian and other pharmacopoeias. The subsequent practical evaluation of the selected conditions used three batches of the herbal medicinal product “Aloe Juice” by Vifitech (batches 131217, 030318 and 070618). The identification was carried out using a silica gel plate for high-performance thin-layer chromatography (HPTLC Silica Gel 60 HX85224933 1056330001 by Merck). The results were examined in daylight before and after spraying with a 2% alcohol solution of sodium hydroxide. The quantification was carried out using a Cary-100 spectrophotometer by Agilent at 512 nm and 0.5% magnesium acetate in methanol as a developing solvent. Results: the authors developed a unified approach to identification and quantification of anthracene-derived compounds in herbal drugs, herbal drug preparations and herbal medicinal products of Aloe arborescens Mill. and suggested using aloe-emodin as a reference standard. The authors established reference values for anthracene-derived compounds in herbal drugs, herbal drug preparations and herbal medicinal products of Aloe arborescens Mill. and drafted the corresponding monographs for the State Pharmacopoeia of the Russian Federation. Conclusions: the developed procedures allow for comprehensive identification and quantification of anthracene-derived compounds in herbal drugs, herbal drug preparations and herbal medicinal products of Aloe arborescens Mill. by the same class of biologically active compounds.